Consensus in Guidelines for Evaluation of DSD by the Texas Children's Hospital Multidisciplinary Gender Medicine Team. (15th August 2010) - Douglas, Ganka; Axelrad, Marni E.; Brandt, Mary L.; Crabtree, Elizabeth; Dietrich, Jennifer E.; French, Shannon; Gunn, Sheila; Karaviti, Lefkothea; Lopez, Monica E.; Macias, Charles G.; McCullough, Laurence B.; Suresh, Deepa; et al.
Abstract : The Gender Medicine Team (GMT), comprised of members with expertise in endocrinology, ethics, genetics, gynecology, pediatric surgery, psychology, and urology, at Texas Children's Hospital and Baylor College of Medicine formed a task force to formulate a consensus statement on practice guidelines for managing disorders of sexual differentiation (DSD) and for making sex assignments. The GMT task force reviewed published evidence and incorporated findings from clinical experience. Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) was used to assess the quality of evidence presented in the literature for establishing evidence-based guidelines. The task force presents a consensus statement regarding specific diagnostic and therapeutic issues in the management of individuals who present with DSD. The consensus statement includes recommendations for (1) laboratory workup, (2) acute management, (3) sex assignment in an ethical framework that includes education and involvement of the parents, and (4) surgical management.